Implementing Scope Squence Planning in PAI Learning: A Case Study at MTsN Gresik - Riezma Diant Amanah; Sayyidah Alfi Nabila; Ahmad Tajuddin Az-Zaki (Indonesian Journal of Islamic Educational Management, 2025)
This study aims to analyze the implementation of scope and sequence in the planning and implementation of Islamic Religious Education (PAI) at MTsN Gresik. Using a qualitative approach with a case study design, data were collected through in-depth interviews, observations, and document analysis. The results of the study reveal three main patterns: systematic learning planning based on CP–TP–ATP, adaptive implementation to classroom dynamics and differences in student abilities, and increased learning effectiveness through material sequencing and the application of diagnostic assessments. The theoretical contribution of this study confirms that scope and sequence is not rigid, but rather a dynamic framework that can be adapted to the needs of students and the context of the madrasah. Practically, this research provides guidelines for PAI teachers in developing a more relevant, structured, and responsive sequence of material. The novelty of this research lies in the integration of scope and sequence with differentiated learning, the flexibility of curriculum implementation in madrasahs that have many incidental activities, and the pattern of sequence adaptation in the subject of Islamic Cultural History